2022
DOI: 10.1017/s1049096522000221
|View full text |Cite
|
Sign up to set email alerts
|

Trump and Trust: Examining the Relationship between Claims of Fraud and Citizen Attitudes

Abstract: Despite winning the presidency in 2016, Donald Trump alleged “millions of illegal votes” and other election fraud. He continued using this rhetoric throughout his tenure as president and ultimately suggested that if he did not win reelection in 2020, it would be because it somehow was stolen from him. Through an original survey experiment, this article explores how such allegations of fraud influence the public’s attitudes toward the conduct of elections, election outcomes, representation, and democracy as a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
(13 reference statements)
2
3
0
Order By: Relevance
“…The Berlinski et al (2021) experiment also provides support for the political congeniality hypothesis according to which fraud claims by partisans will influence co-partisans but not counter-partisans. Similar experimental evidence has been presented by Goodman (2022) as well as Justwan and Williamson (2022). In their survey experiment, Justwan and Williamson (2022) find that claims of fraud lead to significantly lower satisfaction with democracy.…”
Section: Election Fraud and Voterssupporting
confidence: 81%
See 2 more Smart Citations
“…The Berlinski et al (2021) experiment also provides support for the political congeniality hypothesis according to which fraud claims by partisans will influence co-partisans but not counter-partisans. Similar experimental evidence has been presented by Goodman (2022) as well as Justwan and Williamson (2022). In their survey experiment, Justwan and Williamson (2022) find that claims of fraud lead to significantly lower satisfaction with democracy.…”
Section: Election Fraud and Voterssupporting
confidence: 81%
“…Similar experimental evidence has been presented by Goodman (2022) as well as Justwan and Williamson (2022). In their survey experiment, Justwan and Williamson (2022) find that claims of fraud lead to significantly lower satisfaction with democracy. Similarly, Goodman (2022) finds that elite rhetoric regarding electoral manipulation affects citizens' trust in electoral institutions.…”
Section: Election Fraud and Voterssupporting
confidence: 81%
See 1 more Smart Citation
“…Officials like Secretaries of State have witnessed an evolution in their responsibilities from administrators of the vote to crisis communicators who are tasked with providing the public with accurate information about electoral processes and procedures amid a highly fractured information environment (Benson, 2016;Hale & Brown, 2020;Montjoy, 2010). This transition became prominent in 2020, when changes in voting procedures stemming from the Covid-19 and the promoting of electoral conspiracy theories by partisan elites (Benkler et al, 2020;Justwan & Williamson, 2022) required officials to adopt more public roles as defenders of the electoral process (e.g. Meet the Press 2020).…”
Section: Countering Disinformationmentioning
confidence: 99%
“…The narrative of election theft in the 2020 presidential campaign has encouraged ‘Stop the Steal’ protests and rallies that culminated in the United States Capitol attack of January 6, 2021, during which a crowd of pro-Trump supporters disrupted the joint session of Congress assembled to count electoral votes by storming the Capitol building. Justwan and Williamson (2022) found that exposure to election fraud claims was convincing enough to reduce Trump voters’ faith in electoral fairness. As Eggers, Garro and Grimmer (2021 , 6) noted, ‘[t]he Trump campaign delivered a blueprint for losing candidates to undermine support for the winner or even steal the election.…”
Section: Introductionmentioning
confidence: 99%